The Scope for Inflation Targeting in Developing Countries - Savastano, Miguel (IMF Working Papers; Working Paper ;, 1997)
Inflation targeting (IT) serves as monetary policy framework in several advanced economies, where it has enhanced policy transparency and accountability. The paper considers its wider applicability to developing countries. The prerequisites for a successful IT framework are identified as an ability to carry out an independent monetary policy (free of fiscal dominance or commitment to another nominal anchor, like the exchange rate) and a quantitative framework linking policy instruments to inflation. These prerequisites are largely absent among developing countries, though several of them could with some further institutional changes and an overriding commitment to low inflation make use of an IT framework.